2007
DOI: 10.1038/sj.onc.1210736
|View full text |Cite
|
Sign up to set email alerts
|

The ternary complex factor Net/Elk-3 participates in the transcriptional response to hypoxia and regulates HIF-1α

Abstract: The ternary complex factor Net/Elk3 is downregulated in hypoxia and participates in the induction by hypoxia of several genes, including c-fos, vascular endothelial growth factor and egr-1. However, the global role of Net in hypoxia remains to be elucidated. We have identified, in a large-scale analysis of RNA expression using microarrays, more than 370 genes that are regulated by Net in hypoxia. In order to gain insights into the role of Net in hypoxia, we have analysed in parallel the genes regulated by HIF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…Previous studies demonstrated that ELK3 participates in the regulation of various genes, including c-fos, egr-1, and PAI-1. In addition, ELK3 is known as a regulator of HIF-1α expression by modulating HIF-1α stability (21)(22)(23)30,31). HIF-1α plays a key role in the induction of cancer invasion, metastasis and angiogenesis, as well as in cancer growth, glucose metabolism, and other metastasis-associated signaling pathways (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that ELK3 participates in the regulation of various genes, including c-fos, egr-1, and PAI-1. In addition, ELK3 is known as a regulator of HIF-1α expression by modulating HIF-1α stability (21)(22)(23)30,31). HIF-1α plays a key role in the induction of cancer invasion, metastasis and angiogenesis, as well as in cancer growth, glucose metabolism, and other metastasis-associated signaling pathways (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that EMT may play an important role in HCC metastasis. Moreover, recent studies revealed that ELK3 is associated with the regulation of hypoxia-induced factor 1α (HIF-1α) (30,31). HIF-1α is a transcription factor that plays a well-established role in cancer development, progression and metastasis.…”
Section: Elk3 Promotes the Migration And Invasion Of Liver Cancer Stementioning
confidence: 99%
“…Under hypoxia, Hif1a hydroxylation decreases due to reduced PHD abundance and activity (8). We and others have shown that Siah proteins polyubiquitinate PHDs under hypoxic conditions (9,10), thereby targeting them for proteasomal degradation and allowing unmodified Hif-1a protein to dimerize with Hif-1b. The role of Siah proteins in tumor progression is becoming clearer (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of SRF and its cofactors to EC function are poorly understood. In cultured ECs, ELK3 participates in transcriptional responses to hypoxia by regulation of HIF-1α protein stability (28,29). In vitro cultured ECs revealed a role for SRF in VEGF-mediated angiogenesis, actin polymerization, and EC migration (30).…”
Section: Introductionmentioning
confidence: 99%